An Individual’s Perspective of Organisational Change for Sustainability: Role Sensemaking of Corporate (Social) Responsibility & Sustainability Professionals - Gstöhl, Michaela (2017)
This research aims to provide an understanding of the role of Corporate (Social)Responsibility and Sustainability CR&S) professionals and how they make sense of their roles in order to overcome barriers posed in their quest for organisational change towards sustainability. The theoretical premise of this research is based on concepts of sensemaking. For this purpose, semi-structured interviews were conducted with CR&S professionals of different managerial position of various large multinational organisations located in the UK. The findings suggest that CR&S professionals first make sense of their organisational environment, from which they draw cues about posed barriers and possible solutions to overcome these. As such, they use a variety of intra-personal role sensemaking strategies consisting of cognitive, linguistic, and conative approaches to overcome barriers and achieve organisational change towards sustainability. This dissertation ties separate sensemaking elements together and generates a comprehensive understanding of this topic, which builds the foundation for further research to develop upon.